Preparation method of ultrasonic microwave co-assisted temperature-sensitive palladium imprinted polymer
Patent Information
- Application Number
- CN202311511577.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-14
AI Technical Summary
但是现有技术中仅在单一温度场下制备的印迹聚合物存在印迹位点分布不均匀、制备时间长、重现性差、制备条件严苛、单体利用率低等问题
1、将甲壳素颗粒作为高内相Pickering乳液的稳定粒子,使得甲壳素的应用范围进一步扩大。
Smart Images

Figure CN117645696B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional material preparation technology, and relates to a method for preparing thermosensitive palladium-imprinted microspheres, specifically a method for preparing an ultrasound-microwave co-assisted thermosensitive palladium-imprinted polymer. Background Technology
[0002] Palladium possesses excellent catalytic activity, thermal stability, and chemical inertness, playing a crucial role in national defense and technological development. my country has relatively limited palladium reserves and low-grade minerals, while secondary palladium resources contain significantly more palladium than primary minerals. Therefore, recovering palladium from secondary resources is of great significance in ensuring the supply of palladium resources.
[0003] Imprinted polymers, prepared using a special process, leave imprinted cavities with the same spatial structure as the template material and specific adsorption sites. This gives imprinted polymers advantages such as predictable structure, good reusability, high selectivity, and low operational barriers, making them applicable in many fields and showing broad application prospects. However, existing imprinted polymers prepared under a single temperature field suffer from problems such as uneven distribution of imprinted sites, long preparation time, poor reproducibility, stringent preparation conditions, and low monomer utilization. These issues not only affect the application performance of imprinted polymers but also their industrial applications. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing an ultrasonic and microwave co-assisted thermosensitive palladium-imprinted polymer, which can prepare palladium-imprinted microspheres in a short time.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is: a method for preparing an ultrasonic and microwave co-assisted thermosensitive palladium-imprinted polymer, comprising the following steps: 1) Place a beaker containing 3-4g of chitin (practical grade) into a 2L desiccator containing 100-150mL of hydrochloric acid. After sealing the desiccator, fumigate the chitin with hydrochloric acid at 40℃ for 8 hours. After fumigation, rinse the fumigated chitin with a large amount of deionized water until the water is neutral. Then, vacuum dry the chitin at 45℃ to constant weight, pulverize it with a functional pulverizer for 3 minutes, and sieve it to obtain chitin solid particles with a particle size of 250-300 mesh. 2) Take azobisisobutyronitrile (AIBN), 2-methyl-2-(dodecyl trithiocarbonate)propionic acid and N,N-diethylacrylamide in a mass ratio of 1:44 to 45:774.5, and then take ethyl acetate. The mass ratio of ethyl acetate to N,N-diethylacrylamide is 1 to 2:1. Azobisisobutyronitrile, N,N-diethylacrylamide, and 2-methyl-2-(dodecyl trithiocarbonate)propionic acid were dissolved in ethyl acetate, placed in a 25 mL test tube, sealed, and then purged with 99.999% pure nitrogen (N2) at room temperature for 15 minutes. The mixture was then reacted at 70 °C for 36 hours. The product was precipitated with n-hexane to obtain poly(N,N-diethylacrylamide). 3) Take azobisisobutyronitrile, poly(N,N-diethylacrylamide) and acrylamide respectively at a mass ratio of 1:435-437:215-220, and then take N,N-diethylacrylamide and N,N-dimethylformamide (DMF) respectively. The mass ratio of poly(N,N-diethylacrylamide) to N,N-diethylacrylamide is 1:0.365; The mass ratio of poly(N,N-diethylacrylamide) to N,N-dimethylformamide is 1:2.045; Azobisisobutyronitrile, poly(N,N-diethylacrylamide), and acrylamide were dissolved in N,N-dimethylformamide, and then N,N-diethylacrylamide was added. The mixture was placed in a 25 mL test tube, sealed, and then purged with 99.999% pure nitrogen gas at room temperature for 15 minutes. The reaction was carried out at 70 °C for 36 hours. The product was precipitated with the first mixed solution to obtain a thermosensitive block, which is poly(N,N-diethylacrylamide-g-poly(N,N-diethylacrylamide-g-acrylamide)). The first mixed solution is composed of n-hexane and ethyl acetate in a volume ratio of 4:1.
[0006] 4) Take acrylic acid and acrylamide at a mass ratio of 1:0.3-5, and then take ammonium chloropalladium, thermosensitive block, deionized water, soybean oil, ethylene glycol dimethacrylate (EGDMA) and the chitin solid particles obtained in step 1). The mass ratio of ammonium chloropalladium to acrylic acid is 1:10-50; The mass ratio of acrylic acid to the temperature-sensitive block is 1:0.1; The mass ratio of chitin solid particles to deionized water is 1:30 to 90; The mass ratio of acrylic acid to deionized water is 1:5; The volume ratio of deionized water to soybean oil is 1:1 to 4. The volume ratio of ethylene glycol dimethacrylate to deionized water is 1:0.7 to 2.5; Thermosensitive block copolymer, acrylamide, acrylic acid, and ammonium chloropalladate were dissolved in deionized water to obtain a second mixed solution with a mass-volume concentration of 400–1000 g / L. The second mixed solution was placed in a constant temperature shaker and self-assembled for 30 min at 33°C and 200 r / min. Then, chitin solid particles, soybean oil, and ethylene glycol dimethacrylate were added sequentially, and the mixture was stirred for 1–10 min at 8000–13000 r / min at 25°C to obtain a high internal phase Pickering emulsion. 5) Add 0.5–2 mL of the third mixed solution to 10 g of high internal phase Pickering emulsion. First, sonicate the mixture at 100–700 W for 30 min in an ultrasonic-microwave co-reaction workstation, and then react it at 100–700 W for 10–180 min in a microwave power of 100–700 W. After the reaction, elute the oil phase with 95% ethanol solution. Then, elute the template ions with the fourth mixed solution as the eluent. Dry the mixture under vacuum to constant weight to obtain an ultrasonic-microwave co-assisted thermosensitive palladium imprinted polymer. The imprinted polymer is a microsphere with a spherical structure.
[0007] The third mixed solution was prepared by mixing equal volumes of ammonium persulfate solution with a molar volume concentration of 4.382 mmol / L and N,N,N,N-tetramethylethylenediamine solution with a molar volume concentration of 8.606 mmol / L.
[0008] The fourth mixed solution is composed of hydrochloric acid solution and thiourea solution of equal volume and molar volume concentration of 1 mol / L.
[0009] The preparation method of this invention employs an ultrasonic-microwave synergistic reaction workstation for co-assisted polymerization. The presence of the ultrasonic field increases the solubility of the template material and monomers, making the prepolymer mixture system more homogeneous and accelerating the polymerization reaction. Because the ultrasonic cavitation effect may disrupt the self-assembly structure of the functional monomers on the template material, thereby altering the distribution of binding sites, it achieves the generation of more uniform polymer chains and higher yields under mild conditions, and facilitates the formation of spherical nanoparticles. Furthermore, the presence of the microwave field not only shortens the preparation time of the imprinted polymer, reduces reaction byproducts, and improves the selectivity of the imprinted polymer, but also results in products with more uniform particle morphology, shape, and narrow particle size distribution.
[0010] The preparation method of the present invention has the following advantages: 1. Using chitin particles as stabilizing particles in high internal phase Pickering emulsions further expands the application range of chitin.
[0011] 2. A reversible addition-fragmentation chain transfer is used to polymerize thermosensitive monomers to obtain linear thermosensitive blocks. When the external temperature changes, the imprinted pores change due to the sol / gel phase transition of the thermosensitive blocks, thus achieving high-level adsorption and desorption by controlling the temperature.
[0012] 3. Imprinted microspheres were prepared using a composite external field (ultrasonic field + microwave field) to assist in the preparation of the microspheres. By combining the characteristics of the external field, the polymerization reaction time was shortened, the monomer utilization rate was improved, and imprinted microspheres with uniform particle size were prepared.
[0013] 4. By combining high internal phase Pickering emulsion technology, thermosensitive technology, and imprinting technology, thermosensitive imprinted microspheres with a through-pore structure can be prepared in a short time under the combined assistance of ultrasound and microwave, which shortens the preparation time and has a high adsorption rate.
[0014] 5. The obtained thermosensitive palladium-imprinted polymer has a uniform particle size distribution, a short preparation time, a fast adsorption rate, and can achieve high levels of adsorption and desorption by adjusting the temperature. Attached Figure Description
[0015] Figure 1 This is a flowchart of the preparation of the thermosensitive palladium-imprinted polymer in Example 1.
[0016] Figure 2 This is a photograph of the thermosensitive palladium-imprinted polymer prepared in Example 1.
[0017] Figure 3 The thermosensitive palladium-imprinted polymer and its particle size distribution are shown in Example 1.
[0018] Figure 4 This is a graph showing the adsorption and separation performance of the thermosensitive palladium-imprinted polymer prepared in Example 1 at different temperatures.
[0019] Figure 5 This is a diagram showing the reusability of the thermosensitive palladium-imprinted polymer prepared in Example 1. Detailed Implementation
[0020] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0021] Example 1 Place a beaker containing 3 g of chitin into a 2 L desiccator containing 100 mL of hydrochloric acid. After sealing the desiccator, maintain the temperature at 40 ℃ and keep the chitin under hydrochloric acid fumigation conditions for 8 hours. After fumigation, rinse the chitin with a large amount of deionized water until the water is neutral. Then, vacuum dry the chitin at 45 ℃ to constant weight, pulverize it for 3 minutes using a functional pulverizer, and sieve it to obtain chitin solid particles with a particle size of 250-300 mesh. 0.006 g of azobisisobutyronitrile, 0.2664 g of 2-methyl-2-(dodecyl trithiocarbonate)propionic acid, and 4.647 g of N,N-diethylacrylamide were dissolved in 9.294 g of ethyl acetate and placed in a 25 mL test tube. After sealing, 99.999% pure nitrogen gas was passed through the tube at room temperature for 15 minutes. The reaction was carried out at 70 °C for 36 hours. The product was precipitated with n-hexane to obtain poly(N,N-diethylacrylamide) (PDEA). 0.003 g of azobisisobutyronitrile, 1.3098 g of poly(N,N-diethylacrylamide) and 0.6483 g of acrylamide were dissolved in 2.679 g of N,N-dimethylformamide, and then 0.4783 g of N,N-diethylacrylamide was added. The mixture was placed in a 25 mL test tube, sealed, and then purged with 99.999% pure nitrogen gas at room temperature for 15 minutes. The reaction was carried out at 70 °C for 36 hours. The product was precipitated with a mixture of 200 mL of n-hexane and 50 mL of ethyl acetate to obtain the thermosensitive block [poly(N,N-diethylacrylamide-g-poly(N,N-diethylacrylamide-g-acrylamide)], denoted as PDEA-gP(DEA-co-AM). 0.05 g of thermosensitive block, 0.5 g of acrylamide, 0.5 g of acrylic acid and 0.03 g of ammonium chloropalladate were dissolved in 2.5 mL of deionized water to obtain a mixed solution with a mass-volume concentration of 432 g / L. The solution was self-assembled in a constant temperature shaker at 33 °C and 200 r / min for 30 min. Then, 0.05 g of chitin solid particles, 7.5 mL of soybean oil and 1.5 mL of ethylene glycol dimethacrylate were added sequentially, and the mixture was stirred at 13000 r / min at 25 °C for 3 min to obtain a high internal phase Pickering emulsion. Take equal volumes of ammonium persulfate solution with a molar volume concentration of 4.382 mmol / L and N,N,N,N-tetramethylethylenediamine solution with a molar volume concentration of 8.606 mmol / L, and mix them to form a third mixed solution; take equal volumes of hydrochloric acid solution and thiourea solution, each with a molar volume concentration of 1 mol / L, and mix them to form a fourth mixed solution; 1 mL of the third mixed solution was added to 10 g of high internal phase Pickering emulsion. The mixture was first ultrasonically reacted at 500 W for 30 min in an ultrasonic-microwave co-assisted reaction workstation, and then reacted at 500 W for 60 min in a microwave power. After the reaction, the oil phase was eluted with 95% ethanol solution. The template ions were then eluted with the fourth mixed solution. The mixture was dried under vacuum to constant weight to obtain the ultrasonic-microwave co-assisted thermosensitive palladium imprinted polymer, denoted as US / MW-Pd-TIIP.
[0022] Example 1: Flowchart for the preparation of thermosensitive palladium-imprinted polymer, as shown below. Figure 1 As shown. A physical image of the thermosensitive palladium-imprinted polymer prepared in Example 1 is shown. Figure 2 As shown. The particle size distribution of the thermosensitive palladium-imprinted polymer prepared in Example 1 is shown in the figure. Figure 3 . Figure 3 The temperature-sensitive palladium-imprinted microspheres show a uniform particle size distribution, with a particle size distribution of approximately 100 μm.
[0023] Equal volumes of ammonium chloropalladate solution and ferric chloride solution, each with a molar concentration of 1.00 mmol / L, were mixed to form a fifth mixed solution. 0.1 g of the temperature-sensitive palladium-imprinted polymer prepared in Example 1 was added to 20 mL of this fifth mixed solution. The ion concentration in the fifth mixed solution before adsorption was measured using inductively coupled plasma mass spectrometry (ICP-MS). Then, after adsorption at 25°C, 33°C, and 40°C for 240 minutes, the ion concentration after adsorption was measured using ICP-MS. The effect of temperature on the adsorption and separation performance of the temperature-sensitive palladium-imprinted polymer (US / MW-Pd-TIIP) is as follows: Figure 4 As shown, compared to 25 ℃ and 40 ℃, US / MW-Pd-TIIP exhibits a higher adsorption capacity at 33 ℃. Q (Pd) (0.1837 mmol / g) and resolution R (3.2) This is due to the introduction of the thermosensitive block. At 33 °C, the thermosensitive block is in a self-assembled state, and the imprinted pores remain intact. When the external temperature changes, the thermosensitive block undergoes a sol / gel phase transition, causing the imprinted pores to expand and contract, thus increasing its adsorption capacity. Q (Pd) and resolution R Both decrease.
[0024] 0.1 g of the thermosensitive palladium-imprinted polymer prepared in Example 1 was placed in 20 mL of the fifth mixed solution, and the ion concentration in the solution before adsorption was measured using inductively coupled plasma mass spectrometry (ICP-MS). After adsorption at 33°C for 240 minutes, 0.1 g of the adsorbed thermosensitive palladium-imprinted polymer prepared in Example 1 was placed in 1% ammonia solution and desorbed at 25°C for 240 minutes. This adsorption-desorption cycle was repeated 11 times, and the ion concentrations after adsorption and desorption were measured using ICP-MS. After 11 adsorption-desorption cycles, the adsorption amount... Q Resolution D% and resolution R They retained 66.14%, 61.54%, and 81.25% of their original values, respectively. Figure 5 This demonstrates that the thermosensitive palladium-imprinted polymer prepared by the method of the present invention has good reusability.
[0025] 0.1 g of the thermosensitive palladium-imprinted polymer prepared in Example 1 was placed in 20 mL of palladium-containing electroplating solution diluted 400 times. The concentration of each element in the solution before adsorption was determined by inductively coupled plasma mass spectrometry (ICP-MS). After adsorption at 33 °C for 240 minutes, 0.1 g of the adsorbed thermosensitive palladium-imprinted polymer prepared in Example 1 was placed in a mixture of 20 mL of hydrochloric acid solution and thiourea solution (the molar volume concentration of each component before mixing was 1.00 mmol / L). Desorption was carried out at 25 °C for 240 minutes. The concentration of each element in the solution after adsorption and desorption was determined by ICP-MS. The application of ultrasound / microwave co-assisted thermosensitive palladium-imprinted microspheres in actual palladium-containing electroplating solutions diluted 400 times is shown in Table 1.
[0026] Table 1. Application of the thermosensitive palladium-imprinted polymer prepared in Example 1 in actual palladium-containing electroplating solutions after 400-fold dilution. Table 1 shows that the concentration of palladium in the electroplating solution after dilution by 400 times was 0.1172 mmol / L, the concentration of palladium in the solution after adsorption was 0.0004 mmol / L, and the palladium content in the solution after desorption was 0.0961 mmol / L. The thermosensitive palladium-imprinted microspheres prepared by the ultrasonic and microwave co-assisted method of the present invention had an adsorption rate of 99.66% and a desorption rate of 82.28% for palladium.
[0027] Example 2 Place a beaker containing 5 g of chitin into a 2 L desiccator containing 200 mL of hydrochloric acid. After sealing the desiccator, maintain the temperature at 40 °C and keep the chitin under hydrochloric acid fumigation conditions for 8 hours. After fumigation, rinse the chitin with a large amount of deionized water until the water is neutral. Then, vacuum dry the chitin at 45 °C to constant weight, pulverize it, and sieve it to obtain chitin solid particles with a particle size of 250-300 mesh. 0.002 g of azobisisobutyronitrile, 0.0888 g of 2-methyl-2-(dodecyl trithiocarbonate)propionic acid and 1.549 g of N,N-diethylacrylamide were dissolved in 3.098 g of ethyl acetate, placed in a 25 mL test tube, sealed, and then purged with 99.999% pure nitrogen gas at room temperature for 15 minutes. The mixture was then reacted at 70 °C for 36 hours. The product was precipitated with n-hexane to obtain poly(N,N-diethylacrylamide). 0.006 g of azobisisobutyronitrile, 2.619 g of poly(N,N-diethylacrylamide) and 1.296 g of acrylamide were dissolved in 5.356 g of N,N-dimethylformamide. Then, 0.956 g of N,N-diethylacrylamide was added, and 99.999% pure N2 was bubbled through at room temperature for 15 minutes. The reaction was carried out at 70 °C for 36 hours. The product was precipitated with a mixed solution of 200 mL of n-hexane and 50 mL of ethyl acetate to obtain a thermosensitive block, which is poly(N,N-diethylacrylamide-g-poly(N,N-diethylacrylamide-g-acrylamide), denoted as PDEA-gP(DEA-co-AM). 0.05 g PDEA-gP (DEA-co-AM), 0.5 g acrylic acid, 1 g acrylamide, and 0.05 g ammonium chloropalladate were dissolved in 2.5 mL of deionized water to obtain a second mixed solution with a mass-volume concentration of 640 g / L. The second mixed solution was placed in a constant temperature shaker and self-assembled for 30 min at 33 °C and 200 r / min. Then, 0.03 g chitosan, 5 mL soybean oil, and 2.5 mL ethylene glycol dimethacrylate were added sequentially, and the mixture was stirred at 12000 r / min for 5 min to obtain a high internal phase Pickering emulsion. A third mixed solution was prepared by mixing equal volumes of ammonium persulfate solution with a molar volume concentration of 4.382 mmol / L and N,N,N,N-tetramethylethylenediamine solution with a molar volume concentration of 8.606 mmol / L.
[0028] A fourth mixed solution was prepared by mixing hydrochloric acid solution and thiourea solution of equal volume and molar volume concentration of 1 mol / L.
[0029] 1 mL of the third mixed solution was added to 10 g of high internal phase Pickering emulsion. The mixture was first sonicated at 600 W for 30 min in an ultrasonic-microwave co-reaction workstation, and then reacted for another 30 min at 700 W microwave power. After the reaction, the oil phase was eluted with 95% ethanol solution. The template ions were then eluted with the fourth mixed solution. The mixture was dried to constant weight under vacuum conditions and automatically ultrasonic-microwave co-assisted thermosensitive palladium imprinted microspheres were formed. The imprinted polymer is a microsphere with a spherical structure.
[0030] Example 3 Place a beaker containing 4 g of chitin into a 2 L desiccator containing 150 mL of hydrochloric acid, seal the evaporator, and maintain the temperature at 40 ℃ for 8 hours to fumigate the chitin with hydrochloric acid. After fumigation, rinse the fumigated chitin with a large amount of deionized water until the water is neutral. Then, vacuum dry it at 45 ℃ to constant weight, pulverize it for 3 minutes with a functional pulverizer, and sieve it to obtain chitin solid particles with a particle size of 250-300 mesh. 0.004 g of azobisisobutyronitrile, 0.177 g of 2-methyl-2-(dodecyl trithiocarbonate)propionic acid and 3.098 g of N,N-diethylacrylamide were dissolved in 4.647 g of ethyl acetate and placed in a 25 mL test tube. After sealing, nitrogen gas with a purity of 99.999% was passed through the tube at room temperature for 15 minutes. The mixture was then reacted at 70 °C for 36 hours. The product was precipitated with n-hexane to obtain poly(N,N-diethylacrylamide). 0.005 g of azobisisobutyronitrile, 2.183 g of poly(N,N-diethylacrylamide) and 1.080 g of acrylamide were dissolved in 4.464 g of N,N-dimethylformamide, and then 0.797 g of N,N-diethylacrylamide was added. The mixture was placed in a 25 mL test tube, sealed, and then purged with 99.999% pure nitrogen gas at room temperature for 15 minutes. The reaction was carried out at 70 °C for 36 hours. The product was precipitated with a mixed solution of 200 mL of n-hexane and 50 mL of ethyl acetate to obtain a thermosensitive block, which is poly(N,N-diethylacrylamide-g-poly(N,N-diethylacrylamide-g-acrylamide), denoted as PDEA-gP(DEA-co-AM). 0.05 g of thermosensitive block, 1.5 g of acrylamide, 0.5 g of acrylic acid and 0.01 g of ammonium chloropalladate were dissolved in 2.5 mL of deionized water to obtain a second mixed solution with a mass-volume concentration of 824 g / L. The second mixed solution was placed in a constant temperature shaker and self-assembled for 30 min at 33 °C and 200 r / min. Then, 0.04 g of chitin solid particles, 7 mL of soybean oil and 2 mL of ethylene glycol dimethacrylate were added sequentially, and the mixture was stirred at 11000 r / min for 5 min at 25 °C to obtain a high internal phase Pickering emulsion. A third mixed solution was prepared by mixing equal volumes of ammonium persulfate solution with a molar volume concentration of 4.382 mmol / L and N,N,N,N-tetramethylethylenediamine solution with a molar volume concentration of 8.606 mmol / L.
[0031] A fourth mixed solution was prepared by mixing hydrochloric acid solution and thiourea solution of equal volume and molar volume concentration of 1 mol / L.
[0032] 0.5 mL of the third mixed solution was added to 10 g of high internal phase Pickering emulsion. The mixture was first sonicated at 400 W for 30 min in an ultrasonic-microwave co-reaction workstation, and then the reaction was continued at 300 W for 120 min. After the reaction was completed, the oil phase was eluted with 95% ethanol solution. The template ions were then eluted with the fourth mixed solution. The mixture was then vacuum dried to constant weight to obtain an ultrasonic-microwave co-assisted thermosensitive palladium imprinted polymer, which is a microsphere with a spherical structure.
Claims
1. A method for preparing an ultrasound-microwave co-assisted thermosensitive palladium-imprinted polymer, characterized in that, The preparation method comprises the following steps: 1) Fumigate 3-4g of chitin with hydrochloric acid at 40℃ for 8 hours, rinse with deionized water until the rinse water is neutral, then vacuum dry at 45℃ to constant weight, crush, and screen to obtain chitin solid particles. 2) Take azobisisobutyronitrile, 2-methyl-2-(dodecyl trithiocarbonate)propionic acid and N,N-diethylacrylamide in a mass ratio of 1:44 to 45:774.5, and then take ethyl acetate. The mass ratio of ethyl acetate to N,N-diethylacrylamide is 1 to 2:
1. Azobisisobutyronitrile, N,N-diethylacrylamide and 2-methyl-2-(dodecyl trithiocarbonate)propionic acid were dissolved in ethyl acetate, placed in a test tube, sealed, and nitrogen gas was introduced at room temperature for 15 minutes. The reaction was then carried out at 70°C for 36 hours. The product was precipitated with n-hexane to obtain poly(N,N-diethylacrylamide). 3) Take azobisisobutyronitrile, poly(N,N-diethylacrylamide) and acrylamide respectively at a mass ratio of 1:435-437:215-220, and then take N,N-diethylacrylamide and N,N-dimethylformamide respectively. The mass ratio of poly(N,N-diethylacrylamide) to N,N-diethylacrylamide is 1:0.365; The mass ratio of poly(N,N-diethylacrylamide) to N,N-dimethylformamide is 1:2.045; Azobisisobutyronitrile, poly(N,N-diethylacrylamide) and acrylamide were dissolved in N,N-dimethylformamide, and then N,N-diethylacrylamide was added. The mixture was placed in a 25 mL test tube, sealed, and then purged with 99.999% nitrogen gas at room temperature for 15 minutes. The mixture was then reacted at 70 °C for 36 hours. The product was precipitated with the first mixed solution to obtain the thermosensitive block. 4) Take acrylic acid and acrylamide at a mass ratio of 1:0.3-5, and then take ammonium chloropalladium, thermosensitive block, deionized water, soybean oil, ethylene glycol dimethacrylate and the chitin solid particles obtained in step 1). The mass ratio of ammonium chloropalladium to acrylic acid is 1:10-50; The mass ratio of acrylic acid to the temperature-sensitive block is 1:0.1; The mass ratio of chitin solid particles to deionized water is 1:30 to 90; The mass ratio of acrylic acid to deionized water is 1:5; The volume ratio of deionized water to soybean oil is 1:1 to 4. The volume ratio of ethylene glycol dimethacrylate to deionized water is 1:0.7 to 2.5; Thermosensitive block, acrylamide, acrylic acid and ammonium chloropalladate were dissolved in deionized water to obtain a second mixed solution; the second mixed solution was placed in a constant temperature shaker for self-assembly, and then chitin solid particles, soybean oil and ethylene glycol dimethacrylate were added in sequence and stirred at high speed to obtain a high internal phase Pickering emulsion; 5) Add 0.5–2 mL of the third mixed solution to 10 g of high internal phase Pickering emulsion. In an ultrasonic-microwave co-reaction workstation, first sonicate at 100–700 W ultrasonic power for 30 min, then react at 100–700 W microwave power for 10–180 min. Elute the oil phase with ethanol solution. Then elute the template ions with the fourth mixed solution. Vacuum dry to constant weight to obtain an ultrasonic-microwave co-assisted thermosensitive palladium imprinted polymer. This imprinted polymer is a microsphere with a spherical structure. The third mixed solution was prepared by mixing equal volumes of ammonium persulfate solution with a molar volume concentration of 4.382 mmol / L and N,N,N',N'-tetramethylethylenediamine solution with a molar volume concentration of 8.606 mmol / L. The fourth mixed solution is composed of hydrochloric acid solution and thiourea solution of equal volume and molar volume concentration of 1 mol / L.
2. The method for preparing the ultrasonic-microwave co-assisted thermosensitive palladium-imprinted polymer according to claim 1, characterized in that, In step 1), the particle size of the chitin solid particles is 250-300 mesh.
3. The method for preparing the ultrasonic and microwave co-assisted thermosensitive palladium-imprinted polymer according to claim 1, characterized in that: In step 3), the first mixed solution is composed of n-hexane and ethyl acetate in a volume ratio of 4:
1.
4. The method for preparing the ultrasonic and microwave co-assisted thermosensitive palladium-imprinted polymer according to claim 1, characterized in that: In step 4), the self-assembly of the second mixed solution is carried out at a temperature of 33°C and a rotation speed of 200 r / min for 30 min.
5. The method for preparing the ultrasonic and microwave co-assisted thermosensitive palladium-imprinted polymer according to claim 1, characterized in that: In step 4), the second mixed solution self-assembles, and then chitin solid particles, soybean oil and ethylene glycol dimethacrylate are added sequentially. The mixture is then stirred at 25 °C at a speed of 8000-13000 r / min for 1-10 min to obtain a high internal phase Pickering emulsion.